Validation of the FIGO 2009 Staging System for Carcinoma of the Vulva. Issue 3 (1st March 2012) - Tan, Jason; Chetty, Naven; Kondalsamy-Chennakesavan, Srinivas; Crandon, Alex; Garrett, Andrea; Land, Russell; Nascimento, Marcelo; Nicklin, Jim; Perrin, Lewis; Obermair, Andreas
Abstract : Background: The previous (1988) International Federation of Gynecology and Obstetrics (FIGO) vulval cancer staging system failed in 3 important areas: (1) stage 1 and 2 disease showed similar survival; (2) stage 3 represented a most heterogeneous group of patients with a wide survival range; and (3) the number and morphology of positive nodes were not taken into account. Objective: To compare the 1988 FIGO vulval carcinoma staging system with that of 2009 with regard to stage migration and prognostication. Methods: Information on all patients treated for vulval cancer at the Queensland Centre for Gynecological Cancers, Australia, between 1988 to the present was obtained. Data included patients' characteristics as well as details on histopathology, treatments, and follow-up. We recorded the original 1988 FIGO stage, reviewed all patients' histopathology information, and restaged all patients to the 2009 FIGO staging system. Data were analyzed using the Kaplan-Meier method to compare relapse-free survival and overall survival. Results: Data from 394 patients with primary vulval carcinoma were eligible for analysis. Patients with stage IA disease remained unchanged. Tumors formerly classified as stage II are now classified as stage IB. Therefore, FIGO 2009 stage II has become rare, with only 6 of 394 patients allocated to stage II. Stage III has been broken down into 3 substages, thus creating distinct differences in relapse-free survival and overall survival. Prognosis of patients with stage IIIC disease is remarkably poor. Conclusion: The FIGO 2009 staging system for vulval carcinoma successfully addresses some concerns of the 1988 system. Especially, it identifies high-risk patients within the heterogeneous group of lymph node–positive patients.